Spectrophotometric Determination of Various Drugs Using Chloranilic Acid as Chromogenic Reagent - II - V. Annapurna; G. Jyothi; T. Rohini Kumari; B. B. V. Sailaja (E-Journal of Chemistry)
Simple, accurate and reproducible visible spectrophotometric method for the assay of drugs such as pyrilamine and fluvoxamine as maleates was established based on the formation of charge-transfer complex and redox reaction between the corresponding drug and substituted p-benzoquinone (chloranilic acid). The optical characteristics such as Beer’s law limits, molar absorptivity and Sandell’s sensitivity are reported. Regression analysis using the method of least squares was made to evaluate the slope (b), intercept (a) and correlation coefficient (r) and standard error of estimation (Se) for each drug.